Observation of the baryonic decay B0 → [lambda]+cpK-K+ - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We report the observation of the baryonic decay ¯B0→Λ+c¯pK−K+ using a data sample of 471×106 B¯B pairs produced in e+e− annihilations at √s=10.58 GeV. This data sample was recorded with the BABAR detector at the PEP-II storage ring at SLAC. We find B(¯B0→Λ+c¯pK−K+)=(2.5±0.4(stat)±0.2(syst)±0.6B(Λ+c))×10−5, where the uncertainties are statistical, systematic, and due to the uncertainty of the Λ+c→pK−π+ branching fraction, respectively. The result has a significance corresponding to 5.0 standard deviations, including all uncertainties. For the resonant decay ¯B0→Λ+c¯pϕ, we determine the upper limit B(¯B0→Λ+c¯pϕ)<1.2×10−5 at 90% confidence level.
Im Titel sinf die Zeichen + und - sowie die Ziffer 0 hochgestellt
Im Titel sind das B und das p sind oben mit einem Querbalken versehen
Im Titel ist das c ist tiefgestellt
Gesehen am 16.06.2020